Uncovering the Mystery of Financial Failure: Financial and Non-Financial Factors in the Financial Crisis and Their Implications for Sustainable Development Goal 8 - Bandi Bandi; Payamta Payamta; Setianingtyas Honggowati; Nikke Yusnita Mahardini (Journal of Current Studies in SDGs, 2026)
Objective: The aim of this research is to obtain empirical evidence about the impact of ownership structure, CEO characteristics, and accounting ratios on financial distress. This research also examines the implications of financial distress factors for achieving Sustainable Development Goal 8 through maintaining corporate sustainability and economic growth. Method: The research uses multiple regression analysis tests. The research results show that company ownership structure, CEO education, and liquidity ratios make a significant contribution to financial risk, namely financial distress. Other variables, namely age and CEO tenure, do not have a significant effect on financial distress. Results:  This research provides contributions to both academics and practitioners, especially from the perspective of financial distress or bankruptcy studies..  Novelty: The originality of this research is the use of non-financial factors such as ownership structure and CEO characteristics which are associated with the risk of financial distress. Most studies test the ability of financial factors to influence financial distress, while this study integrates financial and non-financial factors to explain the possibility of corporate financial failure and its implications for Sustainable Development Goal 8.